Cytotoxicity and inhibition of P-glycoprotein by selected medicinal plants from Thailand - Noysang, Chanai; Mahringer, Anne; Zeino, Maen; Saeed, Mohamed; Luanratana, Omboon; Fricker, Gert; Bauer, Rudolf; Efferth, Thomas (Journal of ethnopharmacology, 2014)
Ethnopharmacological relevance - Thai medicine has a long tradition of tonifying medicinal plants. In the present investigation, we studied the flower extracts of Jasminum sambac, Mammea siamensis, Mesua ferrea, Michelia alba, Mimusops elengi, and Nelumbo nucifera and speculated that these plants might influence metabolism and substance flow in the body. - Materials and methods - Isolation of porcine brain capillary endothelial cells (PBCECs) as well as multidrug-resistance CEM/ADR5000 leukemia cells, MDA-M;B-231 breast cancer, U-251 brain tumor, and HCT-116 colon cancer cells were used. The calcein-acetoxymethylester (AM) assay was used to measure inhibition of P-glycoprotein transport. XTT and resazurin assays served for measuring cytotoxicity. - Results - The extracts revealed cytotoxicity towards CCRF-CEM leukemia cells to a different extent. The strongest growth inhibition was found for the n-hexane extracts of Mammea siamensis and Mesua ferrea, and the dichloromethane extracts of Mesua ferrea and Michelia alba. The flower extracts also inhibited P-glycoprotein function in porcine brain capillary endothelial cells and CEM/ADR5000 leukemia cells, indicating modulation of the blood-brain barrier and multidrug resistance of tumors. Bioactivity-guided isolation of coumarins from Mammea siamensis flowers revealed considerable cytotoxicity of mammea A/AA, deacetylmammea E/BA and deacetylmammea E/BB towards human MDA-MB-231 breast cancer, U-251 brain tumor, HCT-116 colon cancer, and CCRF-CEM leukemia cells. - Conclusion - The plants analyzed may be valuable in developing novel treatment strategies to overcome the blood-brain barrier and multidrug-resistance in tumor cells mediated by P-glycoprotein.